Profitability analysis of backyard poultry egg production among households in Dutse, Jigawa State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
Backyard poultry production has been widely practiced as an alternative income source. Past researchers on its economics mainly focused on large-scale egg production. Thus, this study aims to analyses Backyard Poultry Egg Production (BPEP) among households in Dutse, Jigawa State of Nigeria for sustainable management A random sampling procedure was used to select and collect data from ninety (90) households in the study area using a structured questionnaire. The data collected was analyzed using descriptive statistics and net farm income (NFI).  Approximately, 60% of the respondents were female. Each household typically consists of an average of 8 members. The respondents have an average age of 32 years and possess an average of 5 years’ experience in BPEP. Over 80% of the respondents were formally educated. Small-scale production of less than 50 birds (65.6%). Most of the eggs produced (86.7%) were consumed within their locality and they expressed a strong willingness to expand their activities (86.7%). The NFI analysis result shows that an average cost of ₦16,261.54 per bird was incurred during the production cycle; most (76.01%) constituted the cost of feed. Revenue of ₦21,996.06 was generated, most (84%) from egg sales with ₦5,734.52 net income (profit) per egg production cycle. Conversely, BPEP was constrained by market fluctuations, high cost of production and lack of innovative training in the study area. Hence, BPEP was concluded to be a profitable household enterprise. It is recommended that household income diversification programmes should target the aspect of backyard poultry production in the study area.
Keywords: Backyard; Egg; Household; Poultry; Production and Profitability